2009
DOI: 10.1097/opx.0b013e3181b2f403
|View full text |Cite
|
Sign up to set email alerts
|

Nearpoint Phorias After Nearwork Predict ADHD Symptoms in College Students

Abstract: Phorias postnearwork, but not prenearwork, predicted self-reported ADHD-related symptoms in college students. These results link binocular imbalance immediately after sustained nearwork to symptoms theorized to result from nearwork-induced visual stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Other studies examine whether or not variability in visual tasks predict non-visual abilities or performance. Orlansky et al (2015) found that variability in astigmatism measured in preschool-aged children predicted various forms of reduced academic readiness in various developmental and educational domains, and Wilmer and Buchanan (2009) found that nearpoint phorias after near work predict ADHD symptoms in college students.…”
Section: The Value Of Research On Individual Differencesmentioning
confidence: 99%
“…Other studies examine whether or not variability in visual tasks predict non-visual abilities or performance. Orlansky et al (2015) found that variability in astigmatism measured in preschool-aged children predicted various forms of reduced academic readiness in various developmental and educational domains, and Wilmer and Buchanan (2009) found that nearpoint phorias after near work predict ADHD symptoms in college students.…”
Section: The Value Of Research On Individual Differencesmentioning
confidence: 99%
“…For this reason, this matter should be investigated, as these subjects have a high visual demand, using their near vision for many hours. Wilmer and Buchanan have found that nearpoint phorias (phorias that differ from the median phoria in either a convergent or divergent direction) measured after near work predict a broad range of symptoms in college students, showing that whatever binocular mechanism is involved (convergence or divergence), the association with symptoms has its effect only after near work and at near point.…”
mentioning
confidence: 99%
“…Although some studies have obtained data on visual symptomatology in university students [23], there are a lack of studies analyzing the negative effects of excessive use of near vision. Due to the high visual demand for several hours [24], it has been observed that near-point measurements after near work are predictive of symptoms in students, which shows that a responsible mechanism produces this symptomatology after a continuous effort in near vision [25].…”
Section: Introductionmentioning
confidence: 99%